PENGARUH PEMBERIAN WARNA CAHAYA LED YANG BERVARIASI TERHADAP KANDUNGAN KAROTENOID BAYAM - Talib, Ferawati (JFT: Jurnal Fisika dan Terapannya, 2018)
This study aims to determine how the effect of varying the color of LED light on the  content of carotenoid red spinach and green spinach, and to know what color produces the highest amount of carotenoids, therefore conducted research by giving 3W LED lighting with the brand sunfree lamp for 12 hours at night in open spaces with red, green, yellow and without lights with a distance of about 7cm for red lights, for green lights with a distance of 14 cm and yellow lights with a distance of 23 cm from the surface of spinach. With the intensity of the lamp 180 lux. Spinach used in this study was red spinach and green spinach. The variables measured in this study were the number of spinach leaves measured every week with temperatures ranging from 22-32 °C. Measurements were made every 7 days (every Friday). Based on the results of the activity, it can be concluded that the effect of light coloration on the levels of red spinach carotenoids on green light is very influential because the highest number of carotenoids is 123.11 μmol / L, because green light has the smallest wavelength of 495-570 nm and has the biggest photon energy is 2.17-2.50 eV. Whereas in the past green green spinach has the smallest amount of carotenoids caused by the color equation which makes the pigment or carotenoid small with carotenoid amounts of 68.46 μmol / L.Keywords: Red spinach, green spinach, UV-vis spectrophotometer, light